Endoscopic retrograde cholangiopancreatography training conditions, results from a pan-European survey: between vision and reality - Hamesch, Karim; Cahyadi, Oscar; Dimitriadis, Stavros; Hollenbach, Marcus; Acedo, Pilar; Ayari, Myriam; Dauvarte, Helena; Dieninyte, Egle; Domislovic, Viktor; Dugic, Ana; Ďuriček, Martin; Elshaarawy, Omar; et al. (United european gastroenterology journal, 2025)
Background Endoscopic retrograde cholangiopancreatography (ERCP) still has a relatively high complication rate, underscoring the importance of high-quality training. Despite existing guidelines, real-world data on training conditions remain limited. This pan-European survey aims to systematically explore the perceptions surrounding ERCP training. Methods A survey was distributed through the friends of United European Gastroenterology (UEG) Young Talent Group network to physicians working in a UEG member or associated states who regularly performed ERCPs. Results Of 1035 respondents from 35 countries, 649 were eligible for analysis: 228 trainees, 225 trainers, and 196 individuals who regularly performed ERCP but were neither trainees nor trainers. The mean age was 43 years, with 72.1% identifying as male, 27.6% as female, and 0.3% as non-binary. The majority (80.1%) agreed that a structured training regimen is desirable. However, only 13.7% of trainees and 28.4% of trainers reported having such a structured program in their institutions. Most respondents (79.7%) supported the concept of concentrating training in centers meeting specific quality metrics, with 64.1% suggesting a threshold of 200 annual ERCPs as a prerequisite. This threshold revealed that 36.4% of trainees pursued training in lower-volume centers performing <200 ERCPs annually. As many as 70.1% of trainees performed <50 annual ERCPs, whereas only 5.0% of trainers performed <50 ERCPs annually. A low individual trainee caseload (<50 ERCPs annually) was more common in lower-volume centers than in higher-volume centers (82.9% vs. 63.4%). Conclusions The first pan-European survey investigating ERCP training conditions reveals strong support for structured training and the concentration of training efforts within centers meeting specific quality metrics. Furthermore, this survey exposes the low availability of structured training programs with many trainees practicing at lower-volume centers and 71% of all trainees having little hands-on exposure. These data should motivate to standardize ERCP training conditions further and ultimately improve patient care throughout Europe.
Online veröffentlicht: 27 November 2024
Gesehen am 11.07.2025